A Decade of FDA-Approved Pharmacophore-Based Small Molecules: Advances in Medicinal Chemistry from 2014 to 2024 - Sanjaykumar, Randhe Siddhant; Basavaraj, Chavan Sagar; Arshad, Anam Sania Md.; Singh, Rohit; Mahindroo, Neeraj (Synlett, 2025)
Over the past decade, the pharmaceutical field has seen significant advancements with the approval of innovative small-molecule drugs by the FDA. These low molecular weight compounds have set new benchmarks in therapy. This review examines their design, medical applications, mechanisms of action, and impact across various areas of medicine. It also emphasizes the key structural features critical to their success, highlighting progress in medicinal chemistry.1 Introduction2 Overview of Small Molecule Therapeutics (2014–2024)3 Pharmacophore Classification and Key Approvals3.1 2014: Foundational Advancements3.2 2015–2016: Addressing Rare and Chronic Diseases3.3 2017–2019: Oncology and Neurological Milestones3.4 2020–2021: Responses to Global Health Needs3.5 2022–2024: Cutting-Edge Innovations3.6 Remdesivir; A Perfect Example of Pharmacophore-Driven Drug Discovery4 Structural and Mechanistic Insights4.1 Structural Determinants4.2 Mechanistic Versatility5 Therapeutic Breakthroughs5.1 Oncological Innovations5.2 Infectious Disease Management5.3 Neurological and Psychiatric Advances5.4 Cardiovascular and Related Advances5.5 Miscellaneous Diseases5.6 Summary6 Challenges and Future Perspectives6.1 Addressing Drug Resistance6.2 Integrating Artificial Intelligence (AI) in Drug Discovery6.3 Precision Medicine6.4 Sustainability in Drug Development7 Conclusion
Keywords: small molecules; FDA; pharmacophore; pharmaceutical chemistry